Looesly packed versus densely packed alloplast in the treatment of periodontal intrabony defects : A clinical and radiographical study - Heba Samir Mahmoud; Eman Yossef Elfirt; Hala Zakaria; Mona Salah Eldin Darhous (Cairo : Heba Samir Mahmoud, 2010)
The present study was designed to compare the clinical and radiographic effectiveness of loosely packed tri - calcium phosphate alloplast versus densely packed alloplast in the management of periodontal intrabony defects . Using a split - mouth design, 20 intrabony defects in 10 patients were divided into 2 groups (A&B)
Thesis (M.Sc.) - Cairo University - Faculty of Oral and Dental Medicine - Department of Oral-Diagnosis
Issued also as CD
Keywords: Bone graft; Loose packing; Periodontal regeneration